'A true European': In Memory of Eberhard 'Paddy' Bort, 1954–2017. Issue 3 (August 2017) - Anderson, Malcolm; Bechhofer, Frank; Brown, Alice; McCrone, David; Relich, Mario
Abstract : Eberhard 'Paddy' Bort served as Reviews Editor of Scottish Affairs from 2000 to his unexpected death in early 2017. This essay draws together several of his colleagues and friends to outline Paddy's contributions to the study of Borders and his wider activities in and around Scottish academic life.